PENGARUH PENGGUNAAN MODEL LEARNING STARTS WITH A QUESTION TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Mustika Helma; Gigin Saipul Rahma (Journal of Didactic Mathematics, 2020)
The study began with observations at VIII Rengat Barat Middle School students of class VIII. This study aims to determine students' mathematical problem solving abilities using the Learnig Starts With A Question model. This type of research is experimental research (experimental research) with a quasi-experimental design research design. The research design used was The Randomized posttest-only control design. The sampling technique uses Simple Random Sampling. In this study the instrument used was a test of students' mathematical problem solving abilities. Data obtained on the problem-solving ability test were analyzed using the Independent Samples T-Test based on the results of the hypothesis test, the value of tcount = 2.014 and ttable = -1.999 with (df) n-2 and significance <0.05 (0.048 <0.05). As for the Independent Samples T-Test testing criteria, reject H0 if t> t table. Based on that, H0 is rejected because tcount = 2,014> ttable = -1,999. So it can be concluded that the students 'mathematical problem solving ability using the Learning Starts With A Question learning model is better than the students' mathematical problem solving ability using the conventional model in class VIII of SMP Negeri 4 Rengat Barat. Keywords: Problem Solving, Learnig Starts With A Question